Expanding the genotype–phenotype correlation of childhood sensory polyneuropathy of genetic origin - Chakravorty, Samya (Sci Rep, 2020)
Pure sensory polyneuropathy of genetic origin is rare in childhood and hence important to document the clinical and genetic etiologies from single or multi-center studies. This study focuses on a retrospective chart-review of neurological examinations and genetic and electrodiagnostic data of confirmed sensory polyneuropathy in subjects at a tertiary-care Children’s Hospital from 2013 to 2019. Twenty subjects were identified and included. Neurological examination and electrodiagnostic testing showed gait-difficulties, absent tendon reflexes, decreased joint-position, positive Romberg’s test and large fiber sensory polyneuropathy on sensory nerve conduction studies in all patients associated with lower-extremity spasticity (6), cardiac abnormalities or cardiomyopathy (5), developmental delay (4), scoliosis (3), epilepsy (3) and hearing-difficulties (2). Confirmation of genetic diagnosis in correlation with clinical presentation was obtained in all cases (COX20 n = 2, HADHA n = 2, POLG n = 1, FXN n = 4, ATXN2 n = 3, ATM n = 3, GAN n = 2, SPG7 n = 1, ZFYVE26 n = 1, FH n = 1). Our single-center study shows genetic sensory polyneuropathies associated with progressive neurodegenerative disorders such as mitochondrial ataxia, Friedreich ataxia, spinocerebellar ataxia type 2, ataxia telangiectasia, spastic paraplegia, giant axonal neuropathy, and fumarate hydratase deficiency. We also present our cohort data in light of clinical features reported for each gene-specific disease subtype in the literature and highlight the importance of genetic testing in the relevant clinical context of electrophysiological findings of peripheral sensory polyneuropathy.